Thrombocytopenic purpura and acute bartonellosis (Carrions Disease) in Huaraz, Peru - López de Guimaraes, Douglas (2006)
We report four cases of acute bartonellosis (positive blood smear for Bartonella bacilliformis), who were present as an important complication, the thrombocytopenic purpura syndrome, a barely described complication for acute bartonellosis. The four cases were hospitalized in the Victor Ramos Guardia Hospital, and all of them are from the endemic zone of Ancash; three are natives and one live 5 years ago in this place. The range of the age was 14 -33 years; the time of the disease, 14-30 days; the parasitic index, 2%-62%. They presented with anemia, fever, epistaxis, petechiae and purpura; two cases had jaundice and hepatoesplenomegaly. The haemoglobin was between 5,6 and 9,7 g/dL; the leukocyte count was between 6 000 to 46 000/mm3 and the platelets were between 5 000 to 20 000/mm3. The direct Coombs test, LE cell test and Elisa for HIV were negative.